The impact of Bisphenol-A on human reproductive health - Esther A. Salami; Oluwakemi A. Rotimi (Toxicology Reports, 2024)
Bisphenol-A (BPA) is a recognized endocrine-disrupting chemical used to produce several consumer goods and products. There has been widespread exposure to BPA because of increased industrial production and use of BPA-containing products. As a result of these exposures, BPA is found in several human body fluids and can cause endocrine disruption by interfering with hormone signaling pathways and epigenetic modifications. Therefore, human reproductive health and development have been adversely affected by BPA. This review aimed to consolidate existing knowledge on the impact of BPA on human reproductive health, examining its effects on both males and females. To achieve this, we systematically searched four databases for studies that associated BPA with reproductive health (male and female), after which we retrieved the important information from the selected articles. There was an association of reproductive health diseases with high BPA exposure. In males, BPA was associated with increased sperm alterations, altered reproductive hormone levels, and testicular atrophy. In females, there was an association of BPA exposure with hormonal imbalances, reduced ovarian reserve, and increased likelihood of conditions such as fibroids, polycystic ovarian syndrome, endometriosis and infertility. BPA's pervasive presence and its harmful effects on reproductive health underscore the need for global regulation and public awareness. Although substantial evidence from animal and in vitro studies supports the detrimental effects of BPA, there is a need for more human-focused research, particularly in developing countries, to confirm these findings. This review advocates for increased regulatory measures to limit BPA exposure.